Technical Development and Agricultural Policy - Dimény, Imre (Acta Agraria Debreceniensis, 2002)
Summarising a study work taken several decades four highly important fields are discussed in this essay: - theoretical and practical methods of technical development, - some special character of the technical development-friendly economic environment, - specialities of the present situation, - preliminary hopes for the future.